Promoting Islamic Values Among Youth Through Mosque-Based Educational Programs in Sibuhuan - Tri Widayatsih (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2024)
This study explores the role of mosque-based educational programs in promoting Islamic values among youth in Sibuhuan, North Sumatra. Utilizing a qualitative descriptive approach, data were collected through observations, interviews, and document analysis involving religious educators, youth participants, and community members. The findings reveal that structured activities such as Qur’an classes, halaqah (study circles), and community service initiatives significantly contribute to the development of moral character, religious discipline, and social responsibility among adolescents. Despite challenges such as limited resources and competition from digital distractions, the mosque remains an effective center for non-formal religious education. The study recommends stronger collaboration between mosques, schools, and local governments to enhance the reach and impact of such programs.